Teacher Professionalism from the Margins: a Critical Discourse Analysis of the policies and politics of governance in England and Sweden - Milner, Alison Louise (2020)
Over a period of thirty years, England and Sweden have implemented large-scale neoliberal ideological reforms of decentralisation, deregulation and privatisation in education. In what is perceived as a shift from government to governance, teacher professionalism is considered a means to steer teachers’ work and education from a distance. However, modes of governance are multiple, multi-scalar and contextually varied and new stakeholders at different scales of coordination have now entered the policy domain. There is therefore a need to understand how governments might mobilise multiple discourses of teacher professionalism for different governance purposes. This thesis compares the dominant policy discourses of teacher professionalism in England and Sweden in the context of wider shifts in educational governance. It identifies the principal policy actors involved in the construction of these discourses and explores whether teacher unions, as a strategic organisational resource of the teaching profession, are marginal and/or central to this process. Employing Jessop’s strategic-relational approach to state theory and concept of meta-governance, alongside Dunsire’s concept of collibration, this project examines how dominant discourses might represent a form of government intervention to ‘tip the scales’ in favour of one or more modes of governance. Located within a critical realist paradigm, it explores how various actors were differentially marginalised and/or privileged in policies and their processes of production. Adopting Critical Discourse Analysis (CDA) as a methodology, this research drew on Fairclough and Van Dijk to analyse two key policy documents: The Importance of Teaching: The Schools White Paper in England and Top of the Class – A New Teacher Education in Sweden. To triangulate the CDA data, semi-structured interviews were conducted with elite policy actors. In England, six dominant discourses of teacher professionalism were identified which could be said to ‘tip the scales’ in favour of the market. In Sweden, four dominant discourses of teacher professionalism were identified which could be said to ‘tip the scales’ in favour of the state. While the shadow state remains important to the legitimation of professional knowledge and status, the shadow market works at the subnational and supranational level in both contexts. In England, teacher unions were marginalised from the policy and its processes of production whereas, in Sweden, one teacher union had privileged epistemic status. This thesis reveals that policy discourses of teacher professionalism are construed largely from the margins of formal policy processes.